2008
DOI: 10.1007/s00438-008-0412-8
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue of Triticum monococcum genes encoding toxic and immunogenic peptides for celiac disease patients

Abstract: The celiac disease (CD) is an inXammatory condition characterized by injury to the lining of the smallintestine on exposure to the gluten of wheat, barley and rye. The involvement of gluten in the CD syndrome has been studied in detail in bread wheat, where a set of "toxic" and "immunogenic" peptides has been deWned. For wheat diploid species, information on CD epitopes is poor. In the present paper, we have adopted a genomic approach in order to understand the potential CD danger represented by storage protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 66 publications
3
29
0
3
Order By: Relevance
“…Small‐intestinal gluten‐specific T‐cell lines from coeliac patients challenged with one T. monococcum accession by proliferation assay triggered heterogeneous responses in a wide range of stimulation indices, thus indicating potential toxicity . Furthermore, the sequencing of T. monococcum cDNA clones related to storage protein genes revealed the presence of four toxic and 13 immunogenic peptides belonging to all storage protein classes, therefore indicating that einkorn has the full potential to induce coeliac disease syndrome.…”
Section: Adverse Reactionsmentioning
confidence: 99%
“…Small‐intestinal gluten‐specific T‐cell lines from coeliac patients challenged with one T. monococcum accession by proliferation assay triggered heterogeneous responses in a wide range of stimulation indices, thus indicating potential toxicity . Furthermore, the sequencing of T. monococcum cDNA clones related to storage protein genes revealed the presence of four toxic and 13 immunogenic peptides belonging to all storage protein classes, therefore indicating that einkorn has the full potential to induce coeliac disease syndrome.…”
Section: Adverse Reactionsmentioning
confidence: 99%
“…Chronic symptoms of celiac disease are intestinal pain, diarrhea, head ache, growth retardation, osteoporosis, infertility, lymphoma, and other diseases. It occurs in genetically susceptible children and adults no less than allergies in most parts of the world (Vader et al, 2003;Wieser, Koehler 2008;Camarca et al, 2009;Cummins, Rob erts Thomson, 2009;Vaccino et al, 2009;Xie et al, 2010;Zingone et al, 2010). Unfortunately, we could not find information in the available literature on the frequency of occurrence of allergies and celiac disease in Russia.…”
Section: Introductionmentioning
confidence: 79%
“…tauschii (Spaenij-Dekking et al, 2005;van Herpen et al 2006;Vaccino et al 2009). Our previous study revealed that the α-gliadin sequences from V genome of Dasypyrum present Glia-α epitope (Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%